English as a Medium of Instruction (EMI) in Learning Practice: Perspectives and Strategies of Educators - Rifiyanti, Hafizah; Dewi, Dyah Utami (Tamaddun Life, 2023)
In Indonesian education, English as an Introductory Language (EMI) is gaining recognition as an approach that uses English as the main language of instruction in schools and universities. EMI is designed to help students improve their English language skills while studying various subjects. This approach has been favored in countries where English is not the mother tongue, offering many advantages, such as preparing students for global communication, improving access to English academic resources, and increasing the competitiveness of educational institutions. However, EMI also provides challenges related to teachers' skills, pedagogical knowledge, and the effectiveness of EMI learning strategies. This study aims to explore the perspectives of 37 educators in Jakarta through descriptive qualitative research on EMI. The educators strongly believe that EMI is an efficient tool to improve student's English proficiency and their understanding of the subject matter. To support the implementation of EMI, this study recommends additional training in EMI, fostering collaboration between experienced and new teachers, and implementing innovative teaching methods. The study concluded that the successful implementation of EMI in the Indonesian educational context depends on the collective commitment of educators, students, educational institutions, and authorities. Continuous support, evaluation, and emotional support for educators and learners are crucial to ensure the effectiveness of EMI in a better education landscape.